Optimizing the long-term management of chronic migraine with onabotulinumtoxinA in real life. (1st February 2018) - Tassorelli, Cristina; Tedeschi, Gioacchino; Sarchielli, P; Pini, Luigi Alberto; Grazzi, Licia; Geppetti, Pierangelo; De Tommaso, Marina; Aguggia, Marco; Cortelli, P; Martelletti, Paolo
ABSTRACT: Introduction : Management of chronic migraine is challenging. OnabotulinumtoxinA (OBT-A) is the only medication licensed for prevention of chronic migraine, and has been widely adopted in clinical practice. Limited data is available on its long-term use. Areas covered : Data from controlled trials are combined with available data on the long-term use of OBT-A in real-life studies, with information obtained in a recent survey among Italian headache centers, and the clinical experience of the authors. Six areas were identified as relevant to patients with chronic migraine: 1) definition of responders to OBT-A; 2) management of responders to OBT-A; 3) optimal timing of prophylaxis with OBT-A; 4) position of OBT-A in prevention of chronic migraine; 5) management of medication overuse, and 6) patient education. Expert commentary : This review provides an update on the latest evidence regarding the long-term use of OBT-A in chronic migraine and analyzes the critical issues in the decision-making process that emerge from the analysis of the literature and routine practice. A treatment algorithm is proposed for the adoption in the daily practice.